2008
DOI: 10.1159/000114859
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Human Leukocyte Antigen DR-DQ Haplotype and Genotype in Type 1 Diabetes in the Japanese Population

Abstract: Aim: This study aims at clarifying the human leukocyte antigen haplotypes and genotypes conferring susceptibility or resistance to type 1 diabetes in the Japanese population. Methods: The frequencies of human leukocyte antigen DR-DQ haplotypes and genotypes were compared between 83 type 1 diabetic patients, except for fulminant type 1 diabetes, and control subjects in the Japanese population. The patients were divided by onset age into four groups (ages 5–14, 15–29, 30–49, and 50–71 years); the haplotype frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
(67 reference statements)
4
26
0
Order By: Relevance
“…The average age at onset of diabetes was relatively low in previous studies (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Maruyama et al, 1994;Tanaka et al, 2002) which did not find a significant susceptibility to DR13 (16-34 years). In contrast, the average age at onset of diabetes was relatively high in previous studies (Katahira et al, 2008;Murao et al, 2004) which did find susceptibility to DR13 (≥35 years). Exploratory analyses revealed that the DR13 haplotype might also confer risk for T1D in subjects in Norway, Sweden (Graham et al, 1999;Undlien et al, 1999), and Venezuela (Balducci-Silano et al, 1994) who do not carry the DR3 or the DR4 haplotype.…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 56%
See 4 more Smart Citations
“…The average age at onset of diabetes was relatively low in previous studies (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Maruyama et al, 1994;Tanaka et al, 2002) which did not find a significant susceptibility to DR13 (16-34 years). In contrast, the average age at onset of diabetes was relatively high in previous studies (Katahira et al, 2008;Murao et al, 2004) which did find susceptibility to DR13 (≥35 years). Exploratory analyses revealed that the DR13 haplotype might also confer risk for T1D in subjects in Norway, Sweden (Graham et al, 1999;Undlien et al, 1999), and Venezuela (Balducci-Silano et al, 1994) who do not carry the DR3 or the DR4 haplotype.…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 56%
“…On the other hand, DRB1*1502-DQA1*0103-DQB1*0601 and DRB1*0803-DQA1*0103-DQB1*0601 haplotypes are present in East Asians, but rare in Caucasians and Blacks (Thomson et al, 2007). These haplotypes confer weak protection against T1D in the Japanese (Katahira et al, 2008;Yasunaga et al, 1996) and Koreans (Park et al, 2000). As with the DQA1*0102-DQB1*0602 haplotype, the DQA1*0103-DQB1*0601 haplotype encodes "non-Arg," an amino acid other than arginine, at position 52 in DQ and aspartic acid at position 57 in DQ .…”
Section: Haplotypes Associated With T1d Protectionmentioning
confidence: 99%
See 3 more Smart Citations